2007
DOI: 10.1021/jp072128+
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Ethyl p-tert-Butylcalix[5]arene Pentanoate and Its Cation Complexes in Nonaqueous Media

Abstract: The solution behavior of ethyl p-tert-butylcalix[5]arene pentanoate, EtCalix(5), in various protic and aprotic solvents has been assessed from the standard Gibbs energies of transfer of this ligand from acetonitrile to other solvents. These data were derived from solubility measurements of EtCalix(5) in different media. It is concluded that in solvents in which metal cation salts are predominant as ionic species in solution (within a low concentration range), the solvation of the ligand will not contribute sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Another benefit of ITC is that a stoichiometry of certain complexation can be easily determined. Many ITC studies have reported ion–dipole interactions between various metal ions and crown ethers, cryptands, and calix[ n ]arenes . In most cases, the complexation of these cyclic Lewis bases with metal ions is enthalpically dominated (Δ H 0 < 0, Δ S 0 < 0), and coordinating solvents such as acetonitrile and N , N -dimethylformamide (DMF) cause an increase in both Δ H 0 and Δ S 0 because of desolvation during complexation.…”
Section: Introductionmentioning
confidence: 99%
“…Another benefit of ITC is that a stoichiometry of certain complexation can be easily determined. Many ITC studies have reported ion–dipole interactions between various metal ions and crown ethers, cryptands, and calix[ n ]arenes . In most cases, the complexation of these cyclic Lewis bases with metal ions is enthalpically dominated (Δ H 0 < 0, Δ S 0 < 0), and coordinating solvents such as acetonitrile and N , N -dimethylformamide (DMF) cause an increase in both Δ H 0 and Δ S 0 because of desolvation during complexation.…”
Section: Introductionmentioning
confidence: 99%
“…If so, this compound can be used as pendant arms in the functionalization of calixarenes and calixpyrroles. This is an area of considerable interest for our Group given the possibility of anchoring this ligand to the polymeric matrices and then being used as recyclable decontaminating agents for removal of heavy metals from water. However before proceeding with these studies, the complexing properties of this compound for these cations need to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…These calculated free energies are reasonable; the Gibbs free energy change for the transfer of 5,11,17,23,29-penta-tert-butyl-31,32,33,34,35calix [5]arene pentaethanoate from ethanol to n-hexane is −5.1 kJ mol −1 based on solubility measurements. 50 In another study, the Gibbs free energy change of solvation for hexane transfer from propanol to n-decane was −4 kJ mol −1 . 51 Thermodynamics of Calixarene Physisorption.…”
Section: ■ Experimental Sectionmentioning
confidence: 96%